2012
DOI: 10.1007/s00262-012-1360-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD8+ T cell proliferation is prognostic for patients with advanced thoracic malignancies

Abstract: There is a complex interplay between the immune system and a developing tumor that is manifest in the way that the balance of T cell subsets in the local tumor environment reflects clinical outcome. Tumor infiltration by CD8(+) T cells and regulatory T cells (Treg) is associated with improved and reduced survival, respectively, in many cancer types. However, little is known of the prognostic value of immunological parameters measured in peripheral blood. In this study, peripheral CD8(+) T cells and Treg from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…5b). We also examined “effector” CD38 hi HLA-DR hi CD8+ T cells, which are activated in an antigen-specific manner as previously reported from studies of chronic viral infection, and are present at elevated levels in cancers including mesothelioma compared with healthy controls [1822]. These cells are predominantly proliferating, and exhibit low expression of Bcl-2 (an anti-apoptotic protein downregulated following antigen-specific T cell activation) [19, 23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). We also examined “effector” CD38 hi HLA-DR hi CD8+ T cells, which are activated in an antigen-specific manner as previously reported from studies of chronic viral infection, and are present at elevated levels in cancers including mesothelioma compared with healthy controls [1822]. These cells are predominantly proliferating, and exhibit low expression of Bcl-2 (an anti-apoptotic protein downregulated following antigen-specific T cell activation) [19, 23].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of cisplatin/pemetrexed are well known, particularly with respect to depletion of proliferating and activated cells as can be observed from our lymphocyte data, and may well alter the immunological background of patients in a manner that can affect the subsequent dose of anti-CD40. We have previously demonstrated a profound reduction in the proportion of Ki67+ CD8+, CD4+ and Treg as well as activated effector CD8+ T cells on day 8 after chemotherapy, which recovers to baseline prior to the next chemotherapy cycle [18]. Thirdly, the effects of the agonistic anti-CD40 antibody, administered on Day 8.…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive roles of lymphocyte subpopulations in peripheral blood were not well studied. McCoy et al [19] found that an elevated proportion of peripheral Treg cells was associated with poor survival in patients with thoracic malignancies. A very recent study has demonstrated that the prognostic value of CD4+ Treg subtypes in NSCLC patients received chemotherapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in NSCLC, increased dendritic, 42 CD4, CD8+, 43,44 macrophages, 45,46 and NK cells 47 suggest a favorable prognosis. On the other hand, increased levels of T-reg 44,48 cells suggest a less favorable prognosis.…”
Section: From Immune Surveillance To Immune Escapementioning
confidence: 99%